2004
DOI: 10.1113/expphysiol.2004.028373
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oestrogen on myofibre size and myosin expression in growing rats

Abstract: This study examined the effect of oestrogen deprivation and replacement on plantaris muscle size and myosin heavy chain (MHC) isoform composition in rats during a period of physiological growth. Seven-week-old female Sprague-Dawley rats were assigned to one of the three treatment groups: (1) control animals (Sham); (2) ovariectomized animals without oestrogen replacement (OVX/CO); and (3) ovariectomized animals with 17β-oestradiol replacement (OVX/E 2 ). OVX/CO and OVX/E 2 animals were pair-fed with Sham anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 33 publications
4
33
0
2
Order By: Relevance
“…Estrogen fed animals consumed less than others (13 vs 15 g/rat per day respectively) which is in accordance with previous studies (Piccone et al 2004). This may contribute to the lowest BW in these rats, but is not the only reason.…”
Section: Animal Modelsupporting
confidence: 79%
See 2 more Smart Citations
“…Estrogen fed animals consumed less than others (13 vs 15 g/rat per day respectively) which is in accordance with previous studies (Piccone et al 2004). This may contribute to the lowest BW in these rats, but is not the only reason.…”
Section: Animal Modelsupporting
confidence: 79%
“…It was demonstrated that ovarian hormone deficiency could play a role in the failure to recover muscle mass after a period of inactivity of the muscle (Sitnick et al 2006). The presence of estrogen receptors in skeletal muscle indicates that skeletal muscle function is also regulated by estrogen (Piccone et al 2004). Changes in hormone concentration have profound influence on muscle fibers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…How the effects of E 2 may differ among fibers with various isoforms of the myosin heavy and light chains is not presently clear, nor is the impact of estrogen status on expression of the various myosin isoforms. There are reports of OVX-related shifts toward slower isoforms/fiber types (11,22,42), toward faster isoforms/fiber types (29,45,61), and no changes in myosin isoforms/fiber types (9,39,42,47,66). Importantly, when such shifts are detected they are modest, in the magnitude of 10% or less, and thus likely have little impact on the extent of force potentiation reported here.…”
Section: Discussionmentioning
confidence: 83%
“…In vitro and in vivo studies with a use of animal models and humans have demonstrated that testosterone stimulates skeletal muscle protein synthesis and increases muscle mass (Grigsby et al, 1976;Griggs et al, 1989;Rooyackers and Nair, 1997;Bhasin et al, 2001). On the other hand, ovarian hormones may inhibit muscle protein synthesis and muscle growth (Toth et al, 2001;McCormick et al, 2004;Piccone et al, 2005). During growth of meat type turkeys under current farming conditions, very rapid skeletal muscle protein synthesis results from intensive anabolic processes of amino acids.…”
Section: Introductionmentioning
confidence: 99%